2020
DOI: 10.1186/s12906-020-2815-y
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology-based study on the mechanism of Yiganling capsule in hepatitis B treatment

Abstract: Background: Yiganling (YGL) capsule is a traditional Chinese medicine preparation consisting of eight herbs that has been clinically proven to have a favorable treatment effect on Hepatitis B (HB). However, due to its multiple targets and multi-pharmacological effects, the mechanisms of YGL capsule in the treatment of HB are unknown. Methods: First, the chemical constituents of YGL capsules were obtained from the Chinese medicine database, and YGL capsules were constructed. Second, active compounds were screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Hepatocyte damage due to HBV infection and the pathogenesis of liver disease is not directly associated with the HBV, however it is caused by the immune-mediated host HBV interactions [33]. The complex mechanisms that cause HBV-mediated liver disease are not fully understood due to the involvement of complex protein-protein interactions with multiple host factors [34].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocyte damage due to HBV infection and the pathogenesis of liver disease is not directly associated with the HBV, however it is caused by the immune-mediated host HBV interactions [33]. The complex mechanisms that cause HBV-mediated liver disease are not fully understood due to the involvement of complex protein-protein interactions with multiple host factors [34].…”
Section: Discussionmentioning
confidence: 99%
“…Network pharmacology is a multidisciplinary approach that utilizes theories from systems biology and pharmacology to investigate the mechanism of action of drugs in the treatment of diseases (Fu et al, 2021; Zhen et al, 2023). An increasing body of research has demonstrated that network pharmacology could systematically and comprehensively elucidate the mechanism of TCM in the treatment of diseases (Liang et al, 2023; Liao et al, 2023; Wang et al, 2023). However, the prototype compounds in herbs online databases used to generate compound–target maps produce false positive results.…”
Section: Introductionmentioning
confidence: 99%
“…Network pharmacology is an emerging approach that integrates network biology with poly-pharmacology [ 17 ]. This concept was presented for the first time in 2007 by pharmacologist Hopkins and was regarded as the next paradigm in drug discovery [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Network pharmacology is an emerging approach that integrates network biology with poly-pharmacology [17].…”
Section: Introductionmentioning
confidence: 99%